Sintomas de ansiedade social em alcoolistas em tratamento ambulatorial: Prevalência, gravidade e preditores - Yoshimi, Nicoli Tamie [UNESP]; Campos, Luana Moraes [UNESP]; Simão, Maria Odete [UNESP]; Torresan, Ricardo Cezar [UNESP]; Torres, Albina Rodrigues [UNESP] (FapUNIFESP (SciELO), 2016)
Objectives: High rates of comorbidity between social anxiety disorder (SAD) and alcohol use disorders have been reported, but the predictors of this comorbidity are poorly known and most studies involve primary SAD samples. The aims were to estimate the prevalence and severity of SAD symptoms among alcohol-dependent patients and to investigate sociodemographic and clinical factors associated with SAD comorbidity, including suicidal behaviors. Methods: A cross-sectional study with 53 adults who were in treatment for alcohol dependence at a Brazilian public university outpatient service. Assessment instruments: Social Phobia Inventory (SPIN), Short Alcohol Dependence Data and Beck Depression Inventory. Bivariate analyses between the categorical outcome (Probable SAD: SPIN = 19) and explanatory variables were conducted. Correlates of SPIN total and subscales scores (dimensional outcomes) were also investigated. Results: The diagnosis and treatment of alcohol dependence occurred, on average, 30 years after the onset of alcohol use and 39.6% of the 53 patients (37 men and 16 women) reported alleviation of social anxiety symptoms with alcohol use. Twenty-four (45.3%) patients presented probable SAD. These patients differed from non-SAD alcohol-dependent individuals by having lower income and higher frequency of depression, suicidal ideation, suicide plans and attempts. The SPIN subscales mostly associated with suicidal behaviors were social inadequacy and social inferiority. Conclusions: SAD symptoms are common among help-seeking alcohol-dependent individuals and should be directly investigated and treated, since depression and suicidality are associated with this comorbidity. Prospective studies are needed to assess the impact of SAD treatment on the clinical course of alcohol dependence.
Social anxiety symptoms in alcohol-dependent outpatients: Prevalence, severity and predictors
Keywords: Alcohol dependence; Alcohol use disorders; Comorbidity; Social anxiety disorder; Social phobia